LEGAL ASSITANCE IN MAKING DOCUMENTS AT FOUNDATION OF LEGAL ASSISTANCE INSTITUTIONS CARE AND NATION'S HOPE - Eghie Mulyadi Purba; Agustianto Agustianto (ConCEPt - Conference on Community Engagement Project, 2022)
LBH is a non-profit legal aid organization established with the aim of providing free legal services (free) to people who need legal assistance but cannot afford it because they are blind or oppressed. Advocates do not have to pay fees, but the client will be responsible for operational costs such as court fees (if the matter is brought to court), if the client is able to pay. LBH, on the other hand, is known to choose matters that will be handled according to its vision and objectives. In handling a case, advocates are required to be able to prepare several documents which are important when a case or case goes to court. There are many documents that must be prepared by a legal expert or advocate to assist clients in resolving a case, especially in civil procedural law, absolute power of attorney. The lack of prudence by the prosecutor opens up opportunities for opponents to make exceptions, and may result in the panel of judges not accepting the lawsuit. Not only in civil procedural law, but also inCriminal procedural law, procedural law for the religious court, procedural law for the state administrative court, procedural law for the Constitutional Court also certainly require a power of attorney or other legal documents, if a client needs and submits the legal assistance to more or other advocate offices.